2009
DOI: 10.1002/dmrr.941
|View full text |Cite
|
Sign up to set email alerts
|

Therapy with GAD in diabetes

Abstract: The enzyme glutamic acid decarboxylase (GAD) is of great importance for the neurotransmission in the central nervous system, and therefore of interest for treatment of pain and neurological disease. However, it is also released in pancreas although its role is not quite clear. GAD is a major auto-antigen in the process leading to type 1 diabetes with both a clear cell-mediated immune response to GAD and auto-antibodies to GAD (GADA), which can be used as a predictor of diabetes. Administration of the isoform G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 69 publications
0
36
0
Order By: Relevance
“…Moreover, the elimination of protease cleavage sites within a protein in order to avoid the generation of intermediates results in less toxicity in mice [109]. The success of antigen-based treatments for autoimmunity might depend on the dose administered, leading to T cell regulation and tolerance [110].…”
Section: Generation Of Protease-resistant Aplmentioning
confidence: 99%
“…Moreover, the elimination of protease cleavage sites within a protein in order to avoid the generation of intermediates results in less toxicity in mice [109]. The success of antigen-based treatments for autoimmunity might depend on the dose administered, leading to T cell regulation and tolerance [110].…”
Section: Generation Of Protease-resistant Aplmentioning
confidence: 99%
“…Alum was selected as an adjuvant for GAD in order to steer away from a Th1-dominated, proinflammatory cellular autoimmune response towards a Th2 response, which favours humoral immunity (antibody production) [10]. Tavira et al demonstrated that individuals who received the influenza vaccination within close proximity of GAD-alum treatment had increased secretion of GAD-induced proinflammatory cytokines, such as IFN-γ and TNF-α, compared with those who received the vaccine further from GAD-alum therapy [5].…”
Section: The Impact Of Influenza Vaccination On Gad-specific Immune Rmentioning
confidence: 99%
“…These include a role for GAD as a possible regulator of pancreatic hormone release, a paracrine signal molecule between endocrine cells in the pancreatic islets or a negative regulator of first-phase insulin secretion. 122 To make it even more complex, this enzyme consists of two isoforms, GAD65 and GAD67 (65 kDa and 67 kDa respectively). 123 Interestingly, several studies already demonstrated a therapeutic capacity of GAD65 in experimental T1D9 models.…”
Section: No Effect 109mentioning
confidence: 99%
“…This conventional adjuvant was chosen because it stimulates a humoral Th2 (T-helper 2) response rather than a cellular pathogenic immune response. 122 A phase two dose-titration study (Subcutaneous GAD65) was designed to assess the general safety profile of GAD-Alum and its possible toxic effect on β-cells.…”
Section: No Effect 109mentioning
confidence: 99%